Effect of light intensity on photosynthesis and antioxidant defense in boron deficient tea plants - Hajiboland, Roghieh; Bastani, Soodabe; Bahrami Rad, Sara (Acta Biologica Szegediensis, 2011)
Tea (Camellia sinensis (L.) O. Kuntze) plants were grown at adequate (46 μM) or low (<2.5μM) boron (B) supply in the nutrient solution under low (LL, 50 μmol m-2s-1), intermediate (IL, 250 μmol m-2s-1) and high (HL, 500 μmol m-2s-1) light intensities. Boron deficiency hardly affected photochemical events under LL conditions, but alleviated reduction of efficiency of photosynthetic energy conversion in IL and HL plants. The optimum light intensity for CO2 as-similation was IL for the young and HL for the old leaves. Activity of ascorbate peroxidase and superoxide dismutase and concentration of proline was lower under IL compared to LL and HL conditions. Compared to the old leaves, in the young leaves photochemical events were more protected under excess light and low B supply. Antioxidant defense system involved in the protection of leaves against excess light under IL conditions while thermal dissipation performed this role under HL conditions. Alleviation of high light stress effect on the photochemical events could be attributed to the B deficiency-induced activation of antioxidant defense system.